2005
DOI: 10.1093/jat/29.7.616
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Liquid Chromatography-Tandem Mass Spectrometry Method for the Simultaneous Determination of 26 Benzodiazepines and Metabolites, Zolpidem and Zopiclone, in Blood, Urine, and Hair

Abstract: A liquid chromatography-tandem mass spectrometry method was developed for the simultaneous quantification of 26 benzodiazepines and metabolites, zolpidem and zopiclone, in blood, urine, and hair. Drugs were extracted from all matrices by liquid-liquid extraction with 1-chlorobutane. Chromatography was achieved using a XTerra MS C18 column eluted with a mixture of methanol and formate buffer. Data were acquired using positive electrospray ionization and multiple reaction monitoring using one precursor ion/produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 42 publications
0
70
0
3
Order By: Relevance
“…It can potentially complement tests done on blood and urine, though in some scenarios hair may be the only matrix available. Hair as a biological matrix has several advantages including ease of sampling, storage, and transportation [64]. In general, detection of Z-drugs in hair is difficult due to the low level of uptake into hair.…”
Section: Analysis and Detection Of Z-drugsmentioning
confidence: 99%
“…It can potentially complement tests done on blood and urine, though in some scenarios hair may be the only matrix available. Hair as a biological matrix has several advantages including ease of sampling, storage, and transportation [64]. In general, detection of Z-drugs in hair is difficult due to the low level of uptake into hair.…”
Section: Analysis and Detection Of Z-drugsmentioning
confidence: 99%
“…In some analytical methods for ZOP the procedure included an enzymatic hydrolyzing step with β-glucuronidase [127,138], mainly because the methods also included benzodiazepines. Another study showed that ZOP metabolites are excreted mainly unconjugated [142].…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Several analytical methods, including high performance liquid chromatography (HPLC), gas chromatography (GC), gas chromatography mass spectrometry (GC-MS), liquid chromatography mass spectrometry (LC-MS) and liquid chromatography tandem mass spectrometry (LC-MS/MS), have been developed for the identification and quantification of ZOP in whole blood, serum and/or plasma [118,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136]. Some assays (HPLC, LC-MS, LC-MS/MS) have also been developed to separate and determine ZOP [127,[137][138][139] and/or its metabolites (NDZOP and ZOPNO) in urine [140][141][142].…”
Section: Occurrence Of Zopiclone In Forensic Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analytical methods for the detection of multiple benzodiazepine drugs in human blood and urine samples have been reported using GC/MS, 7-10 LC/MS, 11,12 and LC/MS/ MS. [13][14][15][16][17][18] Some of these drugs and their metabolites possess polar groups in their molecules that require derivatization prior to GC/MS analysis.…”
mentioning
confidence: 99%